Transformasi Digital Koperasi Syariah : Mengaplikasikan Etika Bisnis Untuk Kepuasan Anggota Benteng Mikro Indonesia - Iti Septi; Sudrajat Sudrajat (IQTISADIE: Journal of Islamic Banking and Shariah Economy, 2025)
The purpose of this study was to determine the influence of Islamic business ethics on customer satisfaction at the Benteng Mikro Indonesia Sharia Cooperative (Kopsyah BMI) branch in Cikupa, Tangerang, Banten. This study used a qualitative descriptive method, with primary data obtained through interviews with Kopsyah BMI employees. The results showed that the Islamic business ethics implemented by Kopsyah BMI are generally in accordance with sharia principles, including fairness for all members, responsibility for trust, and freedom from usury practices. The application of these principles has been proven to increase customer satisfaction and loyalty, as reflected in the increasing number of members each year. In addition, this study also found the role of digital transformation of sharia cooperatives in strengthening the implementation of Islamic business ethics. Through digital services such as a membership information system, sharia payment applications, and online transaction transparency, Kopsyah BMI is able to provide easy access to services, increase accountability, and expand its reach to the community. This digital transformation not only drives operational efficien sustainably.